SOME ASPECTS OF BRONCHO-OBSTRUCTIVE SYNDROME IN CHILDREN AT THE CURRENT STAGE (American Journal of Interdisciplinary Research and Development, 2024)
Broncho-obstructive syndrome in children is clinically manifested by paroxysmal cough, expiratory dyspnea, asthma attacks and is associated with impaired bronchial patency, develops acutely, but can be persistent. The first symptoms: shortness of breath and wheezing syndrome often appear in children at an early age. Differential diagnosis of biofeedback in young children is difficult due to the impossibility of using methods for assessing the function of external respiration, difficulties in obtaining sputum for cytological and bacteriological studies in order to verify the diagnosis. Early diagnosis, which determines the tactics of treatment, largely determines the prognosis of the disease and the choice of preventive measures.